LATE PLEISTOCENE-HOLOCENE OCEANOGRAPHIC VARIABILITY IN THE OKHOTSK SEA: GEOCHEMICAL, LITHOLOGICAL AND PALEONTOLOGICAL EVIDENCE - Gorbarenko S.A.; Gvozdeva I.G.; Southon J.R.; Keigwin L.D.; Cherepanova M.V. (My University, 2004)
Sedimentary, geochemical and paleontological data, extracted from a sediment core taken from the central Okhotsk Sea, record climatic and sedimentary changes over the past 100 ky. Benthic foraminiferal oxygen isotope record and accelerator mass spectrometry (AMS) 14C data provide the basis for the core age chronology. Planktonic and benthic foraminiferal δ18O and δ13C measurements, magnetic susceptibility, ice rafted debris and coarse fraction content, carbonate and organic carbon content, and diatom and pollen spectra show major changes in regional climate, sea surface conditions, ice extent and sedimentary regime, which are correlated with the global glacial–interglacial changes of marine isotope stages (MIS) 1 through 5.3. Regional cooling and intensification of winter sea ice formation during the last glaciation increased the northern shelf surface water density and Sea of Okhotsk Intermediate Water (SOIW) formation. In addition to major Milankovitch-scale changes, lithological, geochemical and paleontological indices also show suborbital oscillations in Okhotsk Sea hydrology, sedimentation and regional climate. These shorter-term oscillations are characterized by coupled maxima in ice rafted debris and sediment coarse fraction (lithodynamic indices, LDI) values and most are associated with cold events involving enhanced winter ice formation and intensification of SOIW and North Pacific intermediate water (NPIW) formation. The terminations of LDI maxima were induced by climate warming and reductions in ice formation, and were accompanied by sharp decreases in planktonic foraminiferal δ18O. During the glacial terminations of MIS 2 and 4, however, the onset of suborbital-scale LDI maxima occurs close to sharp negative δ18O shifts in planktonic foraminifera (δ18Opf) associated with climate warming. In these special cases, the LDI maxima occurred under warm climate and rising sea levels and did not lead to increases in SOIW or NPIW ventilation.
Keywords: The Okhotsk Sea; Paleoenvironment; Late Pleistocene; Hydrological and lithodynamical oscillations; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Pleistocene